PSIKOLOGI PEMBELAJARAN BAHASA INGGRIS PADA ANAK USIA REMAJA - Faridsyah Dzikri Maulana; Septi Gumiandari (Jurnal Salome : Multidisipliner Keilmuan, 2023)
This research aims to analyze the psychological conditions of adolescent children in the development of learning English speaking. The problem studied is the factors that influence the development of English learning in teenagers and its impact on their psychology. The research method used is literature study by searching for and reviewing relevant previous research. The research results show that the psychological condition of adolescent children plays an important role in learning English speaking, especially in terms of motivation, attitude and self-confidence. These findings become a reference for teachers to understand students' psychological conditions and facilitate the learning process in class. Apart from that, this research is also useful for students to overcome difficulties in learning English and for other researchers as a contribution to further understanding of the psychology of English learning among teenagers.